2013
DOI: 10.4103/0974-9233.106393
|View full text |Cite
|
Sign up to set email alerts
|

Type I retinopathy of prematurity in infants with birth weight less than 1251 g: Incidence and risk factors for its development in a nursery in Kuwait

Abstract: Purpose:To report the rate of acute retinopathy of prematurity (ROP) and Type I ROP among infants with birth weight (BW) <1251 g and identify the risk factors for the development of Type I ROP.Materials and Methods:A retrospective review of ROP records of infants with BW <1251 g was performed to identify infants with acute ROP and Type I ROP. Infants with Type I ROP were compared with those without Type I ROP to assess the risk factors for the development of Type I ROP. P < 0.05 was statistically significant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The incidence of type 1 ROP in ELBW infants was reported as 36.4% by Gharaibeh et al [29] and Wani et al [30], which is similar to the rate in the present study. Choo et al reported that 32.9% of ELBW infants reached a stage of ROP requiring laser treatment [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence of type 1 ROP in ELBW infants was reported as 36.4% by Gharaibeh et al [29] and Wani et al [30], which is similar to the rate in the present study. Choo et al reported that 32.9% of ELBW infants reached a stage of ROP requiring laser treatment [24].…”
Section: Discussionsupporting
confidence: 91%
“…The rate of type 1 ROP requiring laser treatment among 235 ELBW infants in the present study was 36.6%; only 1 study (by Hiraoka et al) reported a higher percentage of ELBW infants with severe ROP requiring laser treatment (41%) [ 28 ]. The incidence of type 1 ROP in ELBW infants was reported as 36.4% by Gharaibeh et al [ 29 ] and Wani et al [ 30 ], which is similar to the rate in the present study. Choo et al reported that 32.9% of ELBW infants reached a stage of ROP requiring laser treatment [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, prevalence of various comorbidities with VLBW or VP in neonates was also analyzed. Table 3 summarizes the results (15,16,18,(20)(21)(22)(23)(24)(25)(26). The most prevalent comorbidity in VLBW newborns allocated to sepsis (49.0%; 95%CI: 38.0-59.0) (15) and the least belonged to PVL (3.0%; 95%CI:2.0-5.0) (16,18,20).…”
Section: Resultsmentioning
confidence: 99%
“…ROP remains as one of the causes of preventable childhood blindness worldwide and its incidence varies among different countries ( 52 ). Severe retinopathy of prematurity requires more treatment in Asia and South America than in most Western countries ( 53 ).…”
Section: Resultsmentioning
confidence: 99%